IMPLEMENTASI KEBIJAKAN PELAYANAN PUBLIK DI KANTOR CAMAT TELUK WARU KABUPATEN SERAM BAGIAN TIMUR - RAHAWARIN, MOHAMAD ARSAD (JURNAL BADATI, 2019)
This study aims to determine the implementation of public service policies in the Teluk Waru Sub-District Office, East Seram Regency in terms of indicators of communication, resources, disposition and bureaucratic structure. This research was designed using a qualitative approach. Informants were employees of the Teluk Waru Sub-District Head Office in East Seram District and people who had sufficient knowledge and were able to explain the actual situation about the object of research. Data analysis was carried out qualitatively. The results showed that (1) communication took place well as indicated by the behavior of employees who were friendly, polite and polite, but still constrained by the low public awareness to follow and obey the provisions, (2) employee resources were adequate in terms of quantity, but still needed improve discipline in terms of time and suitability and consistency with the stipulated provisions in completing service tasks to ensure the accountability of employee performance, (3) disposition has been carried out well which is indicated by the high awareness of all elements of leadership and employees on duties, responsibilities and authority as a public servant, (4) the structure of the bureaucracy goes well in accordance with its main duties and functions by implementing the provisions of service activities in accordance with work procedures in each field.